Visualizing the sonic hedgehog gradient in zebrafish embryos. - Loh, Rachel Ann Wen Yuan. (2012)
Sonic Hedgehog (Shh) is a lipid modified protein secreted by the notochord and the floor plate during vertebrate development. It acts as a graded morphogen, inducing the specification of distinct cell identities in the ventral neural tube in a concentration-dependent manner. To study the gradient formation and distribution of Shh, we visualized transgenic zebrafish embryos expressing a fluorescently-labelled Shh protein (Shh.GFP). We first provide evidence that our fusion protein is correctly synthesized and processed in transgenic embryos, and determine its functionality in vivo. Next, we confirm that Shh.GFP is produced in the notochord and the floor plate; is released into the adjacent neural tube via the transmembrane protein, Dispatched-1; and displays punctate patterns of distribution along the ventral midline cells. These punctae appear to concentrate with the primary cilia, thus suggesting that the primary cilia are involved in Shh signal reception in zebrafish embryos. By inhibiting Smoothened, we also show that the target field response to Shh influences its gradient profile. This study, in which we directly observe and manipulate the Shh.GFP gradient in the context of neural tube patterning, provides valuable insights into the mechanisms of Shh morphogen action in vertebrate development.